Regulación en la ley orgánica de transporte terrestre, tránsito y seguridad vial, la rebaja de punto de la licencia de extranjeros - Villagómez Guamán, Alicia Lucila (2014)
According to Article 97 of the Organic Law on Land Transport, Traffic and Road Safety, states, "the scoring system applied to driver's licenses , for cases of committing traffic violations in accordance with this Act is instituted and the relevant Regulations. Driver's licenses will be granted under the scoring system; the time of issue, the document will score points for all categories of driving licenses applicable to those obtaining for the first time, come to renew or change categories. Driver's licenses will be awarded 30 points for their regular 5-year validity period and a point reduction system will be used for each violation" Points are instituted as a mechanism of penalties for traffic violations committed by drivers of motor vehicles according to the Land Transport Act. But it happens that this system is applied only in our country, nothing indicates that the driver's licenses of foreigners that come with international licenses for this system there is no reduction in points. It is necessary that the licenses of such persons is regulated because traffic offenses can be committed by drivers operating vehicles that have licenses issued in our country and foreigners who come with licenses from other countries , as the legal equality should be established to all arriving to commit traffic violations.